Enzymatic Esterification as Potential Strategy to Enhance the Sorbic Acid Behavior as Food and Beverage Preservative - Federico Zappaterra; Daniela Summa; Bruno Semeraro; Raissa Buzzi; Claudio Trapella; Miguel Ladero; Stefania Costa; Elena Tamburini (Fermentation, 2020)
Sorbic acid is the most commonly used preservative in the food industry. The antimicrobial inhibition of sorbic acid could be influenced by its lipophilic nature, which reduces its use in hydrophilic food formulations. Reactions between sorbic acid and glycerol catalyzed by lipases were studied in order to develop a novel sorbic acid derivate with a promising hydrophilic profile. The esterification reaction between sorbic acid and glycerol in a solvent-free system were performed with an immobilized lipase B from Candida antarctica (CALB). The glycerol sorbate product has been tested against S. griseus bacterium and Saccharomyces cerevisiae yeast. Results indicate that the esterification of sorbic acid with glycerol does improve its antimicrobial properties against Saccharomyces cerevisie . The reported results demonstrate that esterification can be used as a strategy to improve the antimicrobial activity of sorbic acid.